The application of voltage sags pattern to locate a faulted section in distribution network - Mokhlis, Hazlie; Li, H.Y.; Khalid, A.R. (Praise Worthy Prize, 2010)
This paper proposes an alternative automated fault location algorithm to locate a faulted section in distribution network using only voltage sag data monitored at the primary substation. A pattern matching approach between simulated voltage sag and measurement is proposed to identify the faulted section. The degree of matching between the actual and simulated one is then used to rank the possible faulted sections. The algorithm has been tested on an actual urban underground distribution network feeder. The results show that most faulted sections can be located by the first attempt. All remaining faulted sections can be found by the second attempt.